Traceable measurement and imaging of the complex permittivity of a multiphase mineral specimen at micron scales using a microwave microscope - Gregory, A.P; Blackburn, J.F.; Hodgetts, T.E.; Clarke, R.N.; Lees, K.; Plint, S.; Dimitrakis, Georgios (Elsevier, 2016)
This paper describes traceable measurements of the dielectric permittivity and loss tangent of a multiphase material (particulate rock set in epoxy) at micron scales using a resonant Near-Field Scanning Microwave Microscope (NSMM) at 1.2 GHz. Calibration and extraction of the permittivity and loss tangent is via an image charge analysis which has been modified by the use of the complex frequency to make it applicable for high loss materials. The results presented are obtained using a spherical probe tip, 0.1 mm in diameter, and also a conical probe tip with a rounded end 0.01 mm in diameter, which allows imaging with higher resolution (≈10 µm). The microscope is calibrated using approach-curve data over a restricted range of gaps (typically between 1% and 10% of tip diameter) as this is found to give the best measurement accuracy. For both tips the uncertainty of scanned measurements of permittivity is estimated to be±10% (at coverage factor k=2) for permittivity ⪝10. Loss tangent can be resolved to approximately 0.001. Subject to this limit, the uncertainty of loss tangent measurements is estimated to be±20% (at k=2). The reported measurements inform studies of how microwave energy interacts with multiphase materials containing microwave absorbent phases.